Interdependent Construction: Translation Techniques and Translation Quality Assessment on Let’s Read Digital Library Children’s Book - Kurnianingtyas Sri Agung, Winantu; Fitriani, Aries (ELTALL: English Language Teaching, Applied Linguistic and Literature, 2024)
This study investigates translation techniques and translation quality in the Let's Read Digital Children's Story Book. Molina and Albir's theory is used to identify translation techniques, and the modification theory of translation assessment is applied to measure the quality of the translated text. A qualitative method was conducted, and documentation was applied to gain the data within five distinctive title stories of 120 sentences. Then, those data were analysed through content analysis. Ten translation techniques of the eighteen were applied in translating the text: literal, addition, modulation, reduction, calque, transposition, description, reformulation, compensation, and borrowing. Meanwhile, these stories are transferred well within almost 74.4% messages of the text was translated accurately. Furthermore, the aspect of the grammatical construction of the text can be replaced into the target text's construction without any destruction. Then, the translated text was mainly understandable for the target readers, for instance, the students at the primary level or young English learners. Based on the findings, it is recommended that Let's Read Digital Library Children's Book be used as media for the primary level in learning English as a second language, especially in learning reading.